A Case of Fenofibrate-Induced Immune Thrombocytopenia: First Report - Agapakis, Dimitris I.; Massa, Eleni V. (Puerto Rico Health Sciences Journal, 2015)
Fenofibrate is widely prescribed as a hypolipidemic drug and is well tolerated by most patients. We present the case of a 40-year-old woman who developed severe immune thrombocytopenia while on fenofibrate treatment. Clinical features included spontaneous bruising on the feet and hands, a purpuric rash, and menorrhagia. All the laboratory results were normal except for the finding of isolated thrombocytopenia. The subsequent evolution was favorable after fenofibrate removal and with the administration of immunoglobulin G (IgG) plus corticosteroids. Drug-induced thrombocytopenia is briefly reviewed, and a possible mechanism responsible for causing this side effect of fenofibrate is suggested. This is the first reported case of fenofibrate-induced immune thrombocytopenia.